What matters most to patients? Participative provider care and staff courtesy - Andrew Van de Ven (The Beryl Institute, 2014)
Although there is growing recognition of the importance of having satisfied patients, we know little about what aspects of care matter most to patients. The sources of patient satisfaction and how care delivery can influence them need more empirical study. The objective of this study was to identify which aspects of a patient’s experience of care are most important to patient satisfaction, and how dimensions of care relate to clinic size, economic performance, and employee job satisfaction. To explore our question, longitudinal survey data were obtained on patients and employees over two years (1996 and 1997). Relationships between patient satisfaction and the two most critical care experience dimensions, clinic size, economic performance, and job satisfaction were examined. As of result, six major dimensions of patients' experience of care were identified: 1) participative provider care, 2) staff courtesy, 3) self-reported sickness, 4) waiting, 5) staff follow-up, and 6) medical explanations. The first two factors, participative provider care and staff courtesy, account for more than 37% of the total variance in patients’ experience of care. Patient satisfaction is negatively and significantly correlated with clinic size but not correlated with job satisfaction, physician productivity, or clinic profitability. The article concludes suggesting that the personal relationships of a patient with his/her doctor and clinic staff are the strongest predictors of patient satisfaction. Patient satisfaction was found to be unrelated to the employee job satisfaction, physician productivity, and clinic economic performance.